Gender variations in the use of hedges in research articles by Malaysian authors / Hartinah Annuar - Annuar, Hartinah (2012)
The primary purpose of this study was to investigate differences in the use of hedges employed by Malaysian writers across three rhetorical sections (abstract, introduction and discussion) of the research article. Hedges are commonly found in research articles because they are among the most important features used in academic writing to help writers qualify their statements. Despite its major role in academic discourse, much lesser attention has been given to the study of gender variations in the use of hedges in academic discourse. The data that formed the corpus of this study was extracted from 30 research articles from the discipline of Education and English Language Teaching (ELT) written by Malaysian authors. The findings indicate that female authors use almost as much hedging devices as their male counterparts. The rhetorical section found to be most hedged is the discussion, followed by the introduction, while the abstract was found to be the least hedged. This corroborates findings from previous studies which point out that most hedges do occur in the discussion and introduction sections of research articles. Exploring further, the independent samples t-test indicated no significant difference in the occurrence of hedging devices across the three rhetorical sections. The findings of the study further reveal that there is no significant difference in the frequency and distribution of hedges used by female and male authors. Interestingly, frequency counts of the top 15 hedge words indicate little variation of hedges used by either gender implying the lack of adequate repertoire of hedging devices. This calls for a more concerted effort in explicitly teaching the poly-pragmatic functions of hedges considered crucial in EAP. Further explorations on cross disciplinary as well as, cross-cultural dimensions in the usage of hedges should be looked into in understanding the writing practices of members of our academic community.